2021
DOI: 10.1371/journal.pone.0249465
|View full text |Cite
|
Sign up to set email alerts
|

HIV epidemic in fishing communities in Uganda: A scoping review

Abstract: Background Fishing communities in many Sub-Saharan African countries are a high-risk population group disproportionately affected by the HIV epidemic. In Uganda, literature on HIV in fishing communities has grown extensively since the first country’s documented case of HIV in a fishing community in 1985. The current study describes the status of the HIV burden, prevention, and treatment in Ugandan fishing communities. Method This scoping review was conducted based on the York Framework outlined by Arksey and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 62 publications
4
24
3
Order By: Relevance
“…However, our results showed that women in the Southern part were less likely to encounter HIV risk factors yet the region has several fishing communities. The finding deviates from previous studies that have labelled such fishing communities as HIV/AIDS hotspots due to various unique risky behaviours in such communities [ 3 , 38 ]. Region and place of residence have been reported in other studies to be associated with multiple sex partners [ 36 ], inconsistent condom use [ 39 ], STIs [ 39 ], and transactional sex [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results showed that women in the Southern part were less likely to encounter HIV risk factors yet the region has several fishing communities. The finding deviates from previous studies that have labelled such fishing communities as HIV/AIDS hotspots due to various unique risky behaviours in such communities [ 3 , 38 ]. Region and place of residence have been reported in other studies to be associated with multiple sex partners [ 36 ], inconsistent condom use [ 39 ], STIs [ 39 ], and transactional sex [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results showed that women in the Southern part were less likely to encounter HIV risk factors yet the region has several shing communities. The nding deviates from previous studies that have labelled such shing communities as HIV/AIDS hotspots due to various unique risky behaviours in such communities [3,34]. Region and place of residence have been reported in other studies to be associated with multiple sex partners [32], condom use [35], STIs [35], and transactional sex [33].…”
Section: Discussioncontrasting
confidence: 91%
“…As is often the case in these FCs, majority of study participants had lower levels of education, not having formally studied beyond 7 years. 39 Education is related to access to maternal health services. 40 , 41 …”
Section: Discussionmentioning
confidence: 99%